Design of substation grounding grid in CFETR - Yuchen Wang; Jiafu Jiang; Yiyun Huang; Junjia Wang (Scientific Reports)
Abstract This paper aims to propose a method for the design of the substation grounding grid in China Fusion Engineering Test Reactor (CFETR). In order to evaluate the safety of the grounding grid, Electrical Transient Analysis Program (ETAP) was used to simulate the fault current, contact voltage, and step voltage, and the results are compared with theoretical calculations to verify the correctness of the design. This will help reduce faults caused by the defects of grounding grid This method is special in that the designed grounding grid not only meets the requirements of relevant standards, but also reduces the number of conductors. During the design process, factors such as voltage level, fault location, and soil resistivity were fully considered to adapt to different occasions. This method can also guide the design and renovation of grounding grids for other buildings in CFETR.